Genetic Recombination and Clonal Selection in DROSOPHILA MERCATORUM - Annest, Joseph L. (1978)
Discrete and continuous generation unisexual populations were established from parthenogenetic D. mercatorum females heterozygous for five visible loci and one electrophoretic locus, which marked all five major chromosome arms. In the first impaternate generation of the discrete generation population, all thirty-two possible recombinant genotypes for the five visible markers were displayed. However, 99% of these individuals were homozygous for all gene markers due to the predominant mode of parthenogenesis called nuclear duplication. Many of these homozygous individuals gave rise to isogenic clones that were compelled to compete with each other in subsequent generations. A detailed analysis of the genetic response of this clonal population showed strong evidence for selection involving epistatic interactions between linked and unlinked loci throughout the genome. The unit of selection is described as being determined as early as the zygotic stage of development.